Overexcitability in Children Aged 8 and 9 in Parents’ Perception. Does Sex Matter? - Małgorzata Jabłonowska; Agnieszka Demianowska; Joanna Łukasiewicz-Wieleba; Wiesława Limont (Przegląd Badań Edukacyjnych, 2022)
Overexcitabilities (OEs) that manifest themselves in intense, emotional, and deep experiencing